PENGARUH KAPABILITAS PERSONAL, PEMANFAATAN TEKNOLOGI, DAN DUKUNGAN MANAJEMEN PUNCAK TERHADAP KINERJA SISTEM INFORMASI AKUNTANSI - Dewa Ayu Ratna Dewi (UNHI Press, 2021)
Information technology is a necessity that can be used to increase the speed, flexibility, integration and accuracy of the resulting information. Accounting information systems provide opportunities for business people to increase efficiency and effectiveness in decision making so as to allow companies to gain a competitive advantage. The use of computers in some cooperatives is still ineffective which is driven by the factor of the lack of ability of employees in the processing of the systems used. This problem may be an obstacle to the performance of the accounting information system for Savings and Loans Cooperatives in Gianyar Regency. This study aims to determine the effect of personal capabilities, technology use and top management support on the performance of the accounting information system in savings and loan cooperatives in Gianyar regency. The research method used is quantitative research methods with primary data obtained from questionnaire data which is measured using a Likert scale. This research was conducted at the Savings and Loans Cooperative in Gianyar Regency. The population in this study were 155 KSPs in Gianyar Regency. The sample used in this study amounted to 28 KSP which was determined by the nonprobability sampling method, namely purposive sampling which uses certain considerations. The data testing technique uses multiple linear regression analysis using the SPSS version 21 for windows program. Based on the results of the research by distributing questionnaires to 93 respondents, it can be concluded that the factors of personal capability, technology utilization, and top management support have a positive and significant effect on AIS performance. This shows that if AIS users want to achieve satisfaction with the system used, they must pay attention to the factors that influence it.